Diseño de un centro tecnológico-cultural como regeneración de la antigua empresa “Los Trigales” en el polígono B.I. del Parque Industrial, Riobamba - Ecuador. - Medina Guillen, Ana Rebeca (2026)
This research addresses the issues arising from the abandonment of the industrial polygon and the urban deterioration resulting from the accelerated growth of the city of Riobamba, in the province of Chimborazo, Ecuador, which has led to the emergence of urban and social voids in the southern sector of the city. In response to this context, a project is proposed that seeks to revalue industrial heritage through the integration of technology, culture, and innovation. An urban diagnosis of the B.I. polygon was conducted through morphological mapping, land-use analysis, connectivity assessment, and an evaluation of the condition of the industrial structures. Additionally, the Cité du Design in France was studied to understand how technology, culture, and sustainability can be integrated within urban regeneration processes. These principles were applied to the project using the TripleHelix model as a tool to boost social linkage between education, industry, and government. Based on this approach, an architectural proposal was developed to adapt eight metallic silos for cultural and recreational purposes, incorporating a technological block, and rehabilitating existing structures to accommodate cultural and administrative spaces. All components were unified through a curved roof that connects the three parts and transforms them into an integrated whole. The project aims to reactivate the area through spaces of innovation, education, and art, transforming an industrial void into the starting point of an active urban centrality. The creation of this Technological-Cultural Center demonstrates how the rehabilitation of existing structures can become a nucleus for urban, social, and educational development in the southern area of Riobamba.